The Impactful Effect of E-Learning Study Method Towards Students Academic Achievements in General - Irma Kartika Wairooy; Alexander Reynard; Muhammad Robih Octodhia; Wan Mahardika Andanu; Puti Andam Suri; Muhammad Edo Syahputra (Bina Nusantara University, 2023)
This study aims to analyze the impact of the online learning or e-learning system on students' academic scores in general. This study uses previous research to review the infrastructure and factors of the E-Learning system in influencing students' academic scores. The research method of this research is using SLR (Systematic Literature Review). Research searches will be carried out on databases of journals that are known to the public, such as Springer, ResearchGate, Scopus, and others. Twenty-seven articles have been screened to fit the research criteria, collected, and reviewed. This study concludes that the E-Learning System gets honest feedback and is ignored, but indirectly has an impact on the actors in teaching and learning activities in the world of education. E-learning systems can provide solutions to problems at hand, but also create unfamiliar problems. The main factor in improving student learning experiences is student academic value. Keyword - E-Learning, Online Platform, Education, Systematic Online Learning, Academic Achievement, non-Academic Achievement